Trees cut down in Amazon - risk analysis - Elton Ribeiro (2010)
This work presents an analysis of the specific risk for operations of cut of trees, framed in the global operations of forest management in Amazon. It is an operation done outdoors, in that, each tree presents a challenge different from the previous, that elapse from parameters as, for instance, the diameter and inclination of the tree, the distribution of the branches, the topography and the floristic distribution in the environment. In this context, an evaluation of occupational risks was made with the Integrated Method of Evaluation of Risks. An operation of trees cut down not controlled, that it is still usual in the region of Amazon was compared with a controlled one in a logic of sustainable development of Amazon forest. The obtained results point out the enormous advantages, in terms of safety and occupational health, that can bring the use of IPE and the integrated management measures.